Duyog Mindanao a participatory space for the living traditions of Mindanao indigenous music - Alano, Jen Abigail; Ray Alex P. Evangelista (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
The rich and diverse musical heritage of Mindanao’s Indigenous communities serves as a cornerstone of cultural identity and a vital channel for intergenerational knowledge transfer. However, these traditions face significant threats from
modernization and technological advancement. This study explores how architecture can address these challenges by proposing a consolidated ‘living’ museum and ethnomusicology center in Poblacion, Davao City, that supports the preservation and transmission of Indigenous music practices. The project draws on intangible heritage preservation frameworks, music appreciation psychology, experiential learning, and the adaptation of traditional oral traditions into contemporary performances and music-making. Framed through the concept of cultural co-creation, the design
positions architecture as a medium for co-creating cultural meaning, inviting users to actively participate in sustaining musical heritage rather than passively consuming it. Apart from appealing to the contemporary audiences, the design also introduces spatial strategies of openness and collaboration, incorporating immersive design approaches to help audiences understand and connect with the cultural significance of the music. Lastly, spatial "layers" of music exposure and interpersonal music-making spaces are utilized to evoke active engagement with the facility’s users. This study serves as a model for intangible heritage preservation, showcasing how community-centric and participatory design principles can revitalize interest in Indigenous music and strengthen cultural ties.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Music -- Preservation; Music -- Mindanao; Music and architecture -- Mindanao